In situ stress and pore pressure in the Kumano Forearc Basin, offshore SW Honshu from downhole measurements during riser drilling. (27th June 2013) - Saffer, D. M.; Flemings, P. B.; Boutt, D.; Doan, M.‐L.; Ito, T.; McNeill, L.; Byrne, T.; Conin, M.; Lin, W.; Kano, Y.; Araki, E.; Eguchi, N.; et al.
Abstract: [1] In situ stress and pore pressure are key parameters governing rock deformation, yet direct measurements of these quantities are rare. During Integrated Ocean Drilling Program (IODP) Expedition #319, we drilled through a forearc basin at the Nankai subduction zone and into the underlying accretionary prism. We used the Modular Formation Dynamics Tester tool (MDT) for the first time in IODP to measure in situ minimum stress, pore pressure, and permeability at 11 depths between 729.9 and 1533.9 mbsf. Leak‐off testing at 708.6 mbsf conducted as part of drilling operations provided a second measurement of minimum stress. The MDT campaign included nine single‐probe (SP) tests to measure permeability and in situ pore pressure and two dual‐packer (DP) tests to measure minimum principal stress. Permeabilities defined from the SP tests range from 6.53 × 10 −17 to 4.23 × 10 −14  m 2 . Pore fluid pressures are near hydrostatic throughout the section despite rapid sedimentation. This is consistent with the measured hydraulic diffusivity of the sediments and suggests that the forearc basin should not trap overpressures within the upper plate of the subduction zone. Minimum principal stresses are consistently lower than the vertical stress. We estimate the maximum horizontal stress from wellbore failures at the leak‐off test and shallow MDT DP test depths. The results indicate a normal or strike‐slip stress regime, consistent with the observation of abundant active normal faults in the seaward‐most part of the basin, and a general decrease in fault activity in the vicinity of Site C0009. Key Points: We report on in situ pore pressure, stress, and permeability measurements Stress magnitudes indicate a transition in stress regime with depth Measured permeabilities are consistent with observed hydrostatic pressure